2020
DOI: 10.1002/adem.201901432
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture of Highly Porous Tubular Alumina Substrates with Anisotropic Pore Structure by Freeze‐Casting

Abstract: Porous substrates play a major role in devices requiring the flow of fluids such as in filters and membranes. Porous substrates are also extensively used for the preparation of inorganic membranes for microfiltration, [1][2][3] desalination, [4][5][6][7] gas separation, [8][9][10][11] and percrystallization processes. [12,13] These inorganic membranes are known as asymmetric membranes as they are conventionally prepared by coating ceramic [14][15][16] or carbon [17][18][19] thin films as top layers on porous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 75 publications
3
16
1
Order By: Relevance
“…The spatial distribution allowed an analysis of the regions where tensile stresses are prevalent, as well as regions with compressive stresses. The tensile stresses found were slightly higher than the ones obtained by Athayde et al 26 . In addition, the honeycomb model was applied to the freeze-cast alumina and proven adequate in predicting the tensile stresses for material failure with tubular geometry.…”
Section: Introductioncontrasting
confidence: 68%
See 4 more Smart Citations
“…The spatial distribution allowed an analysis of the regions where tensile stresses are prevalent, as well as regions with compressive stresses. The tensile stresses found were slightly higher than the ones obtained by Athayde et al 26 . In addition, the honeycomb model was applied to the freeze-cast alumina and proven adequate in predicting the tensile stresses for material failure with tubular geometry.…”
Section: Introductioncontrasting
confidence: 68%
“…Experimental data used for the modeling in this study were already reported by Athayde et al 26 , specifically: porosity by Archimedes' method 27 and pore diameter by mercury intrusion porosimetry (these results were reproduced in the Appendix, Table A1 and Table A2, respectively). In addition, stereological analyses of the scanning electron microscopy (SEM) micrographs (Figure 1a, b) by the mean linear intercept method 28 were also used.…”
Section: Methodsmentioning
confidence: 81%
See 3 more Smart Citations